Dopaminergic Mutations: Within-Family Association and Linkage in Multiplex Alcohol Dependence Families - Hill, Shirley Y. (2008)
Animal and human studies of addiction indicate that the D2 dopamine receptor (DRD2) plays a critical role in the mechanism of drug reward. D2 receptor density in the brains of alcoholics has been shown to be reduced relative to controls. Previous studies of DRD2 in association with alcohol dependence using variation in the TaqI A locus were highly controversial. Recently, a synonymous mutation, C957T, in the coding region of the human DRD2 gene has been identified which appears to have functional effects including alteration in receptor availability. In order to determine if susceptibility to alcohol dependence (AD) within multiplex alcohol dependence families would be altered by the C957T in the coding region of the D2 gene, within-family association was studied in members of Caucasian multiplex alcohol dependence families. Members of control families with no personal alcohol or substance dependence history were included for case/control comparisons. Analyses performed to detect within-family association showed evidence favoring an association for the C957T polymorphism (P = 0.038). Linkage analyses of polymorphisms in this region showed that only the C957T locus remained of interest (P = 0.015). Evidence for the C957T T allele having a role in AD susceptibility at the population level using a case/control comparison was statistically marginal (P = 0.062), but was consistent with the family data results. These results support a role for DRD2 as a susceptibility gene for alcohol dependence within multiplex families at high risk for developing alcohol dependence.